Evidence for Early Pleistocene glaciation from borecore stratigraphy in north-central Alberta - Andriashek, L. D.; Barendregt, René W. (Alberta Energy Regulator, 2016)
Open access Borecores collected from Quaternary sediments in north-central Alberta, Canada, were sampled and studied for paleomagnetic remanence characteristics. A magnetostratigraphy has been established for sediments previously assumed to represent multiple continental (Laurentide) glaciations but for which no geochronology was available. Based on the Quaternary record elsewhere in Alberta and Saskatchewan, it was thought that some of these sediments were deposited during pre-late Wisconsinan glaciations. The Quaternary sedimentary succession of north-central Alberta attains thicknesses up to 300 m within buried valleys and is composed of diamict interbedded with glaciolacustrine and outwash sediments. Most of the sampled units are not accessible from outcrop and their sedimentology and stratigraphy is derived from core data only. In 4 of 16 borecores sampled to date, diamict that correlates with the Bronson Lake Formation till is reversely magnetized, indicating an Early Pleistocene age. Depending on location, this formation is underlain by either Empress Formation sediments or Colorado Group shales, and is overlain by one or more normally magnetized glacigenic sedimentary units of the Bonnyville, Marie Creek, and Grand Centre formations, respectively. This new record of Early Pleistocene glaciation in north-central Alberta places the westernmost extent of earliest Laurentide ice at least 300 km farther west than its previously established limit in the Saskatoon and Regina regions of the Canadian Interior Plains, but still to the east of the maximum extent of the late Wisconsinan (Late Pleistocene) Laurentide Ice Sheet, which extended into the foothills of the Alberta and Montana Rocky Mountains.